Strategi Sekolah dalam Mengatasi Dampak Negatif Media Sosial pada Etika Siswa SMP N 05 Kota Bengkulu - Fadhillah Azztul Zuhri; Apriliani Annisa Fitri; Mustamin Effendi Nasution; Denisa Tri Anggini; Bagas Pratama; Chantika Dea; Alecia Melanda; Aini Nurhaliza; Rina Safitri; Febriani Setianingrum; M. Aziz Arif; Muhamad Ramadan Putra Sadewa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Social media has become an integral part of adolescent life, including that of junior high school students. While it offers benefits in terms of communication and access to information, social media also brings negative impacts on students’ ethical development, such as impolite behavior, the spread of hoaxes, and cyberbullying. This study aims to describe the strategies implemented by SMP Negeri 05 Kota Bengkulu in addressing the negative effects of social media on student ethics. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings reveal that the school implements five main strategies: (1) internal policies such as prohibiting the use of mobile phones during class hours, (2) integration of character education into the curriculum, (3) implementation of digital literacy programs, (4) collaboration with parents in monitoring social media use at home, and (5) positive utilization of social media for publishing student work and promoting digital ethics campaigns. These strategies have proven effective in shaping responsible digital behavior and reinforcing students’ ethical values. These findings align with previous studies that emphasize the importance of character education, digital literacy , and school–parent collaboration in fostering students’ digital ethics. Through an educational and preventive approach, school strategies can serve as an effective solution in addressing ethical challenges in the digital era.